In Silico Analysis of Antiviral Activity of Analog Curcumin Compounds - Mulatsari, Esti; Martati, Titiek; Mumpuni, Esti; Dewi, Nidya Luciana (Jurnal Jamu Indonesia, 2020)
Some studies state that curcumin analog compounds can improve the bioavailability and biological activity of curcumin. One of the methods to predict the bioactivity of curcumin was computational using molecular docking method. This study has done bioactivity tests of curcumin analog compounds as antiviral using the molecular docking method with the software used are PLANTS, YASARA, MarvinSketch, and Pymol for visualization. This study used analog curcumin compounds derived from previous research. This study used five different viral reseptor types. The maraviroc, docosanol, ribavirin, and zanamivir were used as compound control in this research. The validated target protein consists of 5 (five) receptors with PDB codes 1V2I, 4WEG, 2HWI, 2QAD, and 3ALP. Based on this research, compounds that are predicted active as antiviral on each receptors that are: 2,5-bis(3,5-ditertbutyl-4-hydroxy benzyl)cyclopentanone (1V2I), 1,7- diphenyl-1,6-heptadiene-3,5-dione (4WEG), 1,7-bis(3,4-dibenzyloxiphenyl)-1,6-heptadiene-3,5-dione (2HWI), and 2,5-bis(3,5-ditertbutyl-4-hydroxybenzyl)cyclopentanone (3ALP).